Longitudinal Associations among Fathers' Perception of Coparenting, Partner Relationship Quality, and Paternal Stress during Early Childhood. Issue 1 (16th November 2013) - Fagan, Jay; Lee, Yookyong
<x xml:space="preserve">Abstract</x> This study examined the longitudinal and concurrent associations among fathers' perceptions of partner relationship quality (happiness, conflict), coparenting (shared decision making, conflict), and paternal stress. The sample consisted of 6, 100 children who lived with both biological parents at 24 and 48 months in the Early Childhood Longitudinal Study‐Birth Cohort data set. The results showed that there are significant and concurrent associations between fathers' perceptions of the coparenting relationship and paternal stress, and between partner relationship quality and paternal stress. There was also a positive direct longitudinal association between partner relationship conflict and paternal stress. However, we found only one longitudinal cross‐system mediation effect: fathers' perception of coparenting conflict at 48 months mediated the association between partner relationship conflict at 24 months and paternal stress at 48 months. The family practice implications of these findings are discussed.